Vitamin D Levels and Its Influence on Maternal Blood Glucose, Blood Pressure, and Fetal Weight: A Cross-Sectional Study - Hanif Reza; Yulice Soraya; Fadhli Rizal Makarim; Rizki Alfarizi (Indonesian Journal of Obstetrics and Gynecology, 2025)
Objectives: Vitamin D is needed for many physiological functions. Vitamin D deficiency is a global problem, including vitamin D deficiency in pregnancy. Maternal vitamin D deficiency has been associated with an increased risk of adverse gestational outcomes. This cross-sectional study was conducted to assess the influence of vitamin D levels on the maternal blood glucose, blood pressure, and fetal weight. Methods: Twenty-six women with gestational age 12-16 weeks as participants of this study were recruited from two Primary health care in Semarang, Indonesia between September - October 2023. were analyzed for serum 25 hydroxy vitamin D (25 (OH) D ). The samples then were assessed for blood glucose, blood pressure and fetal weight using ultrasonography. Results: The results of the Pearson's correlation rank test for Vitamin D with estimated fetal weight, blood glucose, systolic blood pressure, and gestational ages as covariate showed a value of P>0.05. Statistically, it means that there is no correlation between vitamin D and other variables. Conclusion: Our study showed level of vitamin D has no influence on of blood glucose level, incidence of hypertension, and low fetal weight Keywords: blood pressure, fetal weight, maternal blood glucose, vitamin D